Resort Di Kawasan Hutan Mangrove Rembang dengan Penekanan Arsitektur Neo-Vernakular) - Kurniawan, Hakam, Ir. Alpha Febela Priyatmono, MT (2016)
The many`s of tourism in Rembang it`s a potential but that has not been developed. In the real life todays modern society, leisure has become a necessity of life. It`s closely linked with the flurry faced in their daily lives and thus require activities that are relaxing and calming down. This problem can resolved through recreation an leisure business. Resort can be defined as an inn located in the tourism area and provides facilities for leisure, recreation and sport. Generally reserved for guests who want to relax on holiday for a long stay or who are coming for receation and wanted a change from everyday activies. That are expected to provide facilities on vacation, give a sense of comfort and come out of the routines, utilizing the existing natural potential ai also able to show the cultural or characteristic of the region. Especially in The Rembang city area, the basic concept of planning is required to refer from the local culture. It`s all about the related election emphasis Neo-Vernakular architecture as a conceptual basis in the planing and desain of the resorts in mangrove forest of ashdod as a way out of the problem. Keywords: Resort, Mangrove Forest, Neo-Vernacular